Development of sustainable PPE for higher threat clearance operations by humanitarian organisations - Brown, Laura (Cranfield University Defence and Security, 2024)
In 2020 it was reported that 59 countries and territories were still contaminated by both landmines and other unexploded ordnance. The threats faced by those in the demining industry have increased due to the more frequent use of IEDs. These will generally have a larger charge size than conventional mines. PPE therefore needs to be improved to keep in line with these new threats. Recently there has been a push from industry to include more sustainable materials within armour production, with some already showing some promise within literature. Ramie (Boehmeria nivea) fibres have also been previously used in studies surrounding in soft armour, hard armour, and multi-layered armour system (MAS) and Flax (Linum usitatissimum) has been investigated with regards to hard armour panels. The hard panels manufacture for this project were produced using the vacuum resin infusion method, a low-cost method that is easy enough to be used in low scale operations. A number of different configurations were created, including natural fibre para-aramid and all natural fibre combinations, all of which were subject to different mechanical tests to assess their strengths. The ballistic testing, completed on a single stage light gas gun, showed the 50% Ramie 50% para-aramid panels outperformed all others tested. A significant observation was the different fracture mechanics seen on the back face of each of the panels, something that may have contributed towards their good performance. The all-natural Flax Ramie panels also showed some significant results, with these panels outperforming several other panels which contained para-aramid materials. Future work in this project will include assessing the best performing panels under increased ballistic loads, as well as looking at the suitability aspect of these panels to determine whether they can be potentially recycled once they have been used.
Keywords: Blast; Ballistics; Armour; Demining